The affairs of the home: LGBT+ migrant community navigating physical and digital space in South Africa, during the global COVID-19 pandemic - Fischer, Steffen (My University, 2022)
Home is an architectural space, a place to settle, to be at peace, to live and be free. To establish a home allows us to envisage a greater sense of belonging that transcends scale and borders: a house on a plot of land or community within a suburb, a city within a country or a WhatsApp group existing in digital space. Using architectural tools such as itineraries, thresholds, tectonics, closet, borders and the home, which transcends the physical boundaries of material tectonics, into social ordering – for LGBT+ migrants, home in this paper, is a community that can exist in both physical and digital spaces. This paper also relies on a GoFundMe campaign launched during COVID-19 as a case study for understanding its navigation between the digital and physical space whilst using networks and existing visible connections which the coordinators had within the LGBT+ migrant community and the experiences of two LGBT+ migrants, Thomars and Ola. The closet is a space that exists within the home and can be combined with scale, where the closet extended becomes the home. The metaphor of the closet is used in this paper to explore how LGBT+ migrants navigate the boundaries between physical and digital spaces. Displacement and human mobility enforce the concept of a home where migrants move, are in search of new homes, to be free across borderlines because their homes have made them vulnerable and exposed, because of their sexual orientation or gender identity. The COVID-19 as a triple threat impacted the lives of LGBT+ migrants. The restriction of movement and harsh laws implemented by the South African government meant that occupying physical space placed LGBT+ migrants in vulnerable positions where COVID-19 can be used as a metaphor for the closet. This research seeks to understand how LGBT+ migrants navigated spatial boundaries during COVID-19 whilst exploring concepts of the home and the closet.
A dissertation submitted in partial fulfilment of the requirements for the award of the degree of Master of Arts in Migration and Displacement to the Faculty of Humanities, School of African Centre for Migration and Society, University of the Witwatersrand, 2021